Policy making for Indian planning: essays on contemporary issues in honour of Montek S. Ahluwalia / edited by Sameer Kochhar (New Delhi, 2012)
Distinguished economists provide knowledge of and insight into India$1 (Bs economic growth and development in this Festschrift to one of the country$1 (Bs key figures in economic reform, Montek S. Ahluwalia. A driving force in the liberalization program of the past 20 years, Ahluwalia and his commitment to poverty alleviation and inclusive growth have inspired change and discussion, including the pieces in this compilation. A must-read for students of development economics and political economy, academics, and professionals interested in economic issues of developing countries, this collection of essays covers different drivers of economic growth and development and offers direction for India to become a major player in the global economy. Topics include poverty in India, urbanization and employment, global imbalances, currency wars, innovation and public information infrastructure, and planning in a liberalized economy.s
Keywords: India-Economic policy